Investigating Students’ Nonlinguistic Problems of Speaking - Rizki Hawalaina; Hendra Heriansyah; Tgk Maya Silviyanti (Research in English and Education Journal, 2018)
This study aimed at investigating the nonlinguistic problems of speaking faced by English Education students of Syiah Kuala University. It also tried to find out the causes why they faced those nonlinguistic problems. A descriptive qualitative study was undertaken by giving the fourteen items of questionnaire and interviewing students in order to attain the needed data in this study. The results of the study showed that there were ten nonlinguistic problems faced by students in speaking namely ‘fear of making errors/mistakes’, ‘fear of being ridiculed by friends’, ‘inability to speak spontaneously’, ‘pressure of limited time’, ‘preexisting habit of using Bahasa Indonesia in speaking class’, ‘fear of being mocked by friends’, ‘lack of confident to speak English’, ‘fluency problem’, ‘feeling nervousness’ and ‘uncertainty in using English’. The most frequent problems faced by students were fear of making errors/mistakes and lack of confidence to speak English. Meanwhile, lack of practice was the main reason why most students faced the nonlinguistic problems during speaking. In conclusion, lecturers and students at English Education of Syiah Kuala University still need to overcome a number of nonlinguistic problems to improve students’ speaking performance.